2021
DOI: 10.2166/wqrj.2021.009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of reservoir impoundment on phytoplankton and shoreline vegetation communities using the space-time substitution method

Abstract: The prediction of the influence of reservoir impoundment on water quality and phytoplankton community is the basis of ecological compensation or restoration. The aim of the current study was to predict the effects of reservoir impoundment on phytoplankton and shoreline vegetation communities using the space-time substitution method. The Huangjinxia Reservoir under construction on the Han River was selected as the research object. The space-time substitution method indicated that the average values of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In our preliminary field investigation, we found that the dominant plants around the study area were C. dactylon, A. philoxeroides, and Acorus calamus (Jian et al 2018). This finding was the same as that in some locations in the TGR (Xu et al 2021). Differently, previous researchers focused on the effect of plants on soil nutrients in the case of inundation at a depth of ten or even tens of meters.…”
Section: The Effects Of Wet-dry Cycle On Soil Organic Carbonsupporting
confidence: 75%
See 2 more Smart Citations
“…In our preliminary field investigation, we found that the dominant plants around the study area were C. dactylon, A. philoxeroides, and Acorus calamus (Jian et al 2018). This finding was the same as that in some locations in the TGR (Xu et al 2021). Differently, previous researchers focused on the effect of plants on soil nutrients in the case of inundation at a depth of ten or even tens of meters.…”
Section: The Effects Of Wet-dry Cycle On Soil Organic Carbonsupporting
confidence: 75%
“…This study selected three plants, including C. dactylon (CD), A. philoxeroides (AP), and Acorus calamus (AC), which were dominated in the WLFZ of the Shiquan Reservoir on the Han River (Xu et al 2021). Planting containers was the 50 Â 100 Â 72 cm boxes, of which had 25 kg soils, ensuring that the soil was about 30 cm in thickness and evenly distributed.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation